1972
DOI: 10.1071/bi9721249
|View full text |Cite
|
Sign up to set email alerts
|

Tinctorial Differentiation of the Cell Types in the Pars Anterior of the Sheep

Abstract: Histological methods have been used to study the pars anterior of the sheep in a number of physiological states with the object of identifying the cellular sources of the hormones produced by this gland.It was possible to identify definitely four types of cell. Two of these were acidophils and stained red or orange after Herlant's tetrachrome. The orange cell showed little variation in different physiological states and probably produces growth hormone while the red was active about the time of parturition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1974
1974
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…The distribution of GH cells observed in lactating and weaning ewes was similar to that observed in anoestrus, with a predominance in the dorsocaudal regions of the hypophysis, as described by Tassell & Kennedy (1972), Ortman (1987) and Bernabé et al . 1995–96 ) .…”
Section: Discussionsupporting
confidence: 82%
“…The distribution of GH cells observed in lactating and weaning ewes was similar to that observed in anoestrus, with a predominance in the dorsocaudal regions of the hypophysis, as described by Tassell & Kennedy (1972), Ortman (1987) and Bernabé et al . 1995–96 ) .…”
Section: Discussionsupporting
confidence: 82%
“…Similar results were reported by Smith and Farquhar [1966], and Vila-Porcile et al [1988]. The variation of granule size during lactation agrees with the postulated process of PRL synthesis and release, and has also been reported by Tassell and Kennedy [1972] in sheep and Navarro [1987] in goats. However, Sá nchez et al [1992] found no such variation in goats.…”
Section: Discussionsupporting
confidence: 80%
“…Bugnon and Garnet (1969) described the initial occurrence of prolactin cells in 20 week old human fetuses, and also observed hypertrophy of these cells from 32 weeks to the time of birth. Presence of fetal prolactin has also been reported in sheep (Stokes andBoda 1968, Tassel1 andKennedy 1972), in mouse (Kohmoto and Bern 1971) and in rat (Setalo 1973). Although the present report does not offer any data on the presence of prolactin before birth, it is worth emphasizing that there is a wide gap between the latest prenatal stage and the neonatal stages employed in this study.…”
Section: Discussionmentioning
confidence: 79%